FGF, Mechanism of Action, Role in Parkinson’s Disease, and Therapeutics - Liu, Yiqiu; Deng, Junyu; Liu, Ye; Li, Wei; Nie, Xuqiang (Frontiers in Pharmacology, 2021)
Parkinson's disease (PD) is a neurodegenerative disease associated with severe disability and adverse effects on life quality. In PD, motor dysfunction can occur, such as quiescence, muscle stiffness, and postural instability. PD is also associated with autonomic nervous dysfunction, sleep disorders, psychiatric symptoms, and other non-motor symptoms. Degeneration of dopaminergic neurons in the substantia nigra compact (SNPC), Lewy body, and neuroinflammation are the main pathological features of PD. The death or dysfunction of dopaminergic neurons in the dense part of the substantia nigra leads to dopamine deficiency in the basal ganglia and motor dysfunction. The formation of the Lewy body is associated with the misfolding of α-synuclein, which becomes insoluble and abnormally aggregated. Astrocytes and microglia mainly cause neuroinflammation, and the activation of a variety of pro-inflammatory transcription factors and regulatory proteins leads to the degeneration of dopaminergic neurons. At present, PD is mainly treated with drugs that increase dopamine concentration or directly stimulate dopamine receptors. Fibroblast growth factor (FGF) is a family of cellular signaling proteins strongly associated with neurodegenerative diseases such as PD. FGF and its receptor (FGFR) play an essential role in the development and maintenance of the nervous system as well as in neuroinflammation and have been shown to improve the survival rate of dopaminergic neurons. This paper summarized the mechanism of FGF and its receptors in the pathological process of PD and related signaling pathways, involving the development and protection of dopaminergic neurons in SNPC, α-synuclein aggregation, mitochondrial dysfunction, and neuroinflammation. It provides a reference for developing drugs to slow down or prevent the potential of PD.